Solar photocatalytic mineralization of antibiotics using magnetically separable NiFe2O4 supported onto graphene sand composite and bentonite. (December 2016) - Gautam, Sourav; Shandilya, Pooja; Singh, Virender Pratap; Raizada, Pankaj; Singh, Pardeep
Graphical abstract: Highlights: Magnetic NiFe2 O4 was staked graphene sand composite and bentonite. Photocatalytic activity of photocatalyst was tested for antibiotic removal. The photocatalysts were magnetically separated from reaction solution. Simultaneous adsorption and photo catalysis process was the most efficient. Power law was applied to explore mineralization kinetics. Abstract: Adsorbent supported photocatalysis is developing as a potential waste water treatment technology. In this work, NiFe2 O4 was supported onto graphene sand composite (GSC) and bentonite (BT) supported to prepare magnetic NiFe2 O4 /GSC and NiFe2 O4 /BT nanocomposties. Graphene sand composite (GSC) was prepared by graphitization of sugar over river sand. The size of NiFe2 O4 /BT and NiFe2 O4 /GSC was found to be 50 and 60 nm respectively. Mesoporous nature of prepared photocatalysts was confirmed by BET adsorption/desorption experiments. NiFe2 O4 /GSC and NiFe2 O4 /BT exhibited ferromagnetic behaviour and could be separated from treated water using external magnetic field. The band gaps of NiFe2 O4 /GSC and NiFe2 O4 /BT were found to be 2.41 and 2.42 eV, respectively. The adsorption and photocatalytic activity of NiFe2 O4 /GSC and NiFe2 O4 /BT was tested for the mineralization of ampicillin (AMP) and oxytetracycline (OTC) antibiotics under solar light. The adsorption process had significant effect on the mineralization of AMP and OTC. Simultaneous adsorption and degradation (A + P) process were the most efficient for antibiotic degradation. The complete mineralization of antibiotics was obtained using NiFe2 O4 /GSC/A + P and NiFe2 O4 /BT/A + P catalytic processes. The kinetics of mineralization were explored using power law model. Magnetically recoverable NiFe2 O4 /GSC and NiFe2 O4 /BT are recyclable and displayed significant recycle efficiency and quick recovery for 10 consecutive catalytic cycles.